The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.11606/1982-8837254529
|View full text |Cite
|
Sign up to set email alerts
|

Developing Historical Competency: Teaching German History Through History Films At University Putra Malaysia (BA German Programme)

Abstract: History films personalize, dramatize and emotionalize historical events and characters. They revive the past by exemplifying it in the present, engage ongoing discourses of history and as a result have proven to be the most influential medium in conveying history to large audiences. History films are regarded as an attractive, motivating and efficient (supplementary) teaching and learning medium in history as well as in foreign language classes. As part of the course “Historical Survey of Germany” (BA German-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Further, the studies by Davison (2017) and Schaar and Wen (2021) provide insight into how an approach inspired by historical literacy may contribute to the development of democratic citizenship. Davison (2017) found that focusing on empathy, exploring historical evidence, and building contextual knowledge in textual encounters were important to enable students to form critical and informed opinions about the past.…”
Section: Previous Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the studies by Davison (2017) and Schaar and Wen (2021) provide insight into how an approach inspired by historical literacy may contribute to the development of democratic citizenship. Davison (2017) found that focusing on empathy, exploring historical evidence, and building contextual knowledge in textual encounters were important to enable students to form critical and informed opinions about the past.…”
Section: Previous Researchmentioning
confidence: 99%
“…Davison (2017) found that focusing on empathy, exploring historical evidence, and building contextual knowledge in textual encounters were important to enable students to form critical and informed opinions about the past. Similarly, Schaar and Wen (2021) found that providing instructions on how to encounter a text and concrete questions targeting both affective and cognitive dimensions were essential to help their students reflect and discuss ethical issues.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation